1992
DOI: 10.1063/1.107568
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of TiN films on (100) silicon substrates by laser physical vapor deposition

Abstract: We report epitaxial growth of TiN films having low resistivity on (100) silicon substrates using pulsed laser deposition method. The TiN films were characterized using x-ray diffraction, Rutherford backscattering, four-point-probe ac resistivity, high resolution transmission electron microscopy and scanning electron microscopy techniques and epitaxial relationship was found to be 〈100〉 TiN ∥ 〈100〉 Si. TiN films showed 10%–20% channeling yield. In the plane, four unit cells of TiN match with three unit cells of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
121
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(126 citation statements)
references
References 10 publications
3
121
1
1
Order By: Relevance
“…The interface between the film and the sapphire is sharp and free from any other phase. Due to the large in-plane mismatch (-18%) between the film and the substrate, the epitaxial growth of the film occurs via domain epitaxy where dimensions of the domain become the repeat distance across which matching is maintained [7]. The misfit dislocations were observed at the interface as shown in Fig.4 (b).…”
Section: Results and Disscusionmentioning
confidence: 81%
“…The interface between the film and the sapphire is sharp and free from any other phase. Due to the large in-plane mismatch (-18%) between the film and the substrate, the epitaxial growth of the film occurs via domain epitaxy where dimensions of the domain become the repeat distance across which matching is maintained [7]. The misfit dislocations were observed at the interface as shown in Fig.4 (b).…”
Section: Results and Disscusionmentioning
confidence: 81%
“…As displayed in Fig. 1(b), the ϕ-scan patterns of (111) It should be noted that the epitaxial growth of BST/LSMO/MgO/TiN on Si (100) is possible due to the epitaxial growth of large mismatched system based on the domain matching epitaxy (DME) paradigm, 14,15 e.g., TiN (a = 4.24 A • ) on Si (100) (a = 5.43 A • ) where four lattice constants of TiN match with three of Si (100). According to DME paradigm, in large mismatch systems most of the lattice mismatch strain is relieved almost immediately upon initiation of growth, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Narayan et.al [19,20] has showed that a large lattice misfit relative to the substrate can still grow epitaxial layers, which is called 'domain matching epitaxy (DME)', where integral multiples of the lattice constants make a good lattice matching between the substrate and the over-grown layer [21]. DME occurs preferably if the surfaces of the substrate and the film have similar crystal structures (i.e.…”
Section: Introductionmentioning
confidence: 99%